(untitled) - Gomez-Mejia, Luis R. (Boston, 2008)
"Management 3rd Edition", by Gomez-Mejia, Balkin, and Cardy, is an exciting new take on principles of management. Ask your incoming students what "management" is, and they'll talk about the kind of management they know from their own work experience. Managers assign people their hours, they give raises or promotions, they tell people what job to do - the manager, in other words, is "the boss". In most other work settings, however, management means something far more important and complex. In addition to people, managers also manage performance, processes, relationships, and more increasingly in today's world, deal with the pressure and flux of constant change.This, coupled with the fact that workplaces have steadily become less hierarchical and more team - and group-driven, means the traditional responsibilities of the manager have gradually been dispersed throughout the organization. Students preparing to work in today's business environment may not start in a corner office with an assistant, but they still need to think like managers and understand the strategic goals of the organization. "Management 3rd Edition", prepares your students to join a new kind of workplace, one where management is everyone's business and provides many in-text and online applications to emphasize this approach.
Keywords: Management,Quản lý